Hubungan Usia Menarche dengan Usia Menopause - Erfiani Mail; Farida Yuliani (JURNAL KEBIDANAN, 2021)
Menopause and menarche are very natural events and definitely happen to a woman. The theory states that the age of menarche is related to the age at menopause. But the existing phenomenon is that currently many women experience menopause at a slower pace, even though several decades ago they experienced a lot of slow menarche, so it should be possible to predict when they experience early menopause. Therefore, researchers are interested in examining the relationship between the age of menarche and the age of menopause. This type of research is analytic observational, with cross sectional design, the population used is all women who have menopause as many as 200 people. The sampling technique used simple random sampling, obtained a sample size of 67 respondents. Data collection uses primary data with a check list instrument. Data analysis used the Spearman rank test, with a significance value of 5% (0.05). The results of this study showed that 14 respondents (20.9%) experienced menarche tarda and normal menopause, 17 menarche with normal menopause, 10 menarche tarda early menopause (14 9%). The results of the Spearman rank analysis of the relationship between the age of menarche and the age of menopause, the rho value is -0.388 with a tcount of 3.394 (t table = 1.998). Ho is rejected if tcount ≥ ttable. This means 3,394> 1,998. This shows that there is a relationship with a negative correlation. It is concluded that there is a relationship between the age of menarche and the age of menopause with a negative correlation. Where if someone experiences precocious menarche age, there is a tendency to experience menopause at an older age and vice versa if someone experiences menarche tarda then they tend to experience early menopause. The age of menopause is influenced by many factors, including psychological factors, heredity, number of children, age at birth, use of contraception, socioeconomic conditions, chronic disease, age of menarche. And it turns out that the age of menarche is still related to the age of menopause. This can be used as an input for a woman to prepare herself for menopause.